2012
DOI: 10.1175/bams-d-11-00129.1
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Volunteer Effort of Scientific Peer Reviewing

Abstract: A survey of reviewers at Monthly Weather Review shows how they perform their reviews and allows a calculation of how much volunteer effort goes into producing a scientific journal. W e are always amazed by the huge effort and the degree of seriousness that peer reviewers bring to the task of reading submitted manuscripts and writing reviews-a voluntary task that takes time away from their own research, other work responsibilities, and personal time. By providing written comments on manuscripts that have been s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Publications are related to scientists' recruitment and promotion, grant funding, invitations to speak at conferences, establishment of collaborations, and media coverage. If the time of review work done by scientists is transformed to money estimated by salary, the annual expenses may add up to more than 2 million euros per international journal (Golden & Schultz, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Publications are related to scientists' recruitment and promotion, grant funding, invitations to speak at conferences, establishment of collaborations, and media coverage. If the time of review work done by scientists is transformed to money estimated by salary, the annual expenses may add up to more than 2 million euros per international journal (Golden & Schultz, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The current double-blind review system works in parallel with the quantitative markers of research quality (bibliometrics), such as impact factors, citations, downloads in databases, views in social media, and journal rankings (Golden & Schultz, 2012;Hirschauer, 2015;Wani & Zainab, 2017;Wellcome Trust, 2015;Wicherts, 2016). Metric practices do not directly serve authors' actual needs to write a methodologically coherent research article.…”
Section: Pr As Critical Appraisal From the Developmental Viewpointmentioning
confidence: 99%
“…According to Kovanis et al's (2016) analysis, an even higher number of manuscripts could be peer reviewed, which indicates that the biomedics field does not suffer from a peer review crisis. Research in other fields such as ecology (Petchey et al, 2014), meteorology (Golden, & Schultz, 2012), science (Vines, Rieseberg, & Smith, 2010), and science and technology (House of Commons Science and Technology Committee, 2011) supports this result. However, we do not know if we can generalize these results to the IS field and conclude that there IS peer review does not suffer from a crisis.…”
Section: Increases In Scholarly Journals Papers and Researchersmentioning
confidence: 91%
“…The most productive reviewers-defined as those who review more than six manuscripts in a year-completed 79 percent of all reviews and averaged almost twice as many reviews per year (i.e., 14.3) compared with eight manuscripts per year for less active reviewers (Ware & Monkman, 2008). Similarly, researchers have report referee overloading to exist in other fields (Golden & Schultz, 2012; House of Commons Science and Technology Committee, 2011; Petchey et al, 2014). Golden and Schultz (2012) report that the number of reviews completed per year, in the meteorology field, averages eight per year.…”
Section: Is Is Peer Review In Crisis?mentioning
confidence: 99%
“…Peer review pipelines are already facing an exploding number of journal article submissions and grant applications (Miller and Couzin 2007). A recent survey by Golden and Schultz (2012) of reviewers for the publication Monthly Weather Review found that reviewers already review an average of eight journal articles per year, spending on average 9.6 h per review. No comparable study has been done specifically looking at the time and effort required to perform data peer review, although anecdotal evidence suggests that in some cases the this effort might be considerably less than 9.6 h (Callaghan 2015).…”
Section: Data Peer Reviewmentioning
confidence: 99%